Correlation between mild cognitive impairment and flourishing among Chinese residents: a cross-sectional study - Lv, Hangqin; Yi, Xin; Guo, Xiangjun; Lin, Meichuan; Bai, Dingxi; Nie, Xingyu; Wang, Xue; Liu, Xiaoyun (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to investigate the correlation between mild cognitive impairment and flourishing among Chinese residents.MethodsA total of 527 community residents aged ≥18 years were recruited from December 2023 to April 2024. Based on the results of the Ascertain Dementia 8-Item Informant Questionnaire (AD8), participants were classified into a healthy group (n = 356) and a mild cognitive impairment (MCI) group (n = 171). General demographic data, including age, gender, height, weight, place of residence, education level, marital status, household composition, personal income, occupation, and the flourishing scale (FS) were collected for statistical analysis. The analysis was performed using Statistical Product and Service Solutions software. Chi-square test was used to compare differences between the groups, while Kendall’s correlation analysis and multivariate logistic regression were applied to assess the relationship between flourishing and MCI.ResultsComparisons between the healthy and MCI groups showed that the FS scores in the healthy group were significantly higher than those in the MCI group (p < 0.01). Kendall’s correlation analysis revealed that the score of AD8 was negatively correlated with FS (r = −0.237, p < 0.01). Multivariate analysis indicated that age [odds ratio (OR) = 1.451, 95% confidence interval (CI; 1.107–1.902), p = 0.007], place of residence [OR = 5.523, 95% CI (3.572–8.539), p < 0.001], and FS [OR = 0.421, 95%CI (0.311–0.569), p < 0.001] were correlated with MCI.ConclusionFlourishing levels are negatively correlated with MCI, and higher levels of flourishing associated with a lower risk of MCI. This suggests that flourishing may serve as a protective factor against cognitive decline. Additionally, age and place of residence are identified as risk factors for MCI.